Application of Epidemiology and Statistical methods in understanding disease aetiology-study on Vitiligo. - Bharat Bhavsar (Healthline, 2010)
The disease results from the interaction between the person’s genetic make up and his outer environment.1 The proportionate role of both the factors varies from disease to disease. There are some diseases with unclear aetiology; Vitiligo is one of them. The purpose of this paper is to show the application of Epidemiology and the statistical methods to understand the disease causation. The epidemiological study of skin conditions among school children in Urban and Rural areas of Surat district carried out by the author 2,3 brought out following observations........